Adaptive control of uncertain systems with input saturation - Visnur K. Muthaiya (2015)
The purpose of this report is to describe the knowledge and the experience the author had gained during this final year project. This report introduces the basic concepts and techniques such as standard-backstepping technique, virtual control laws and the Lyapunov functions. Furthermore this report explains the methodologies such as how the virtual control laws were used to obtain the Lyapunov functions to achieve stability in the system. This report also explains the purpose of introducing the functions of the parameter estimator equations in systems with unknown parameters. An illustration process using an example was used in detail to show the effectiveness of the proposed adaptive controller scheme using Simulink software in order to achieve low tracking errors at the output of the non-linear systems with input saturation. Towards the end, observations and comparisons were made based on the results from the simulation. And finally this report concludes the difficulties the author had experienced during this project and the recommendations the author had put forth for future work in this field of study.